Effect of Neodymium Doping on MRI Relaxivity of Gadolinium Oxide Nanoparticles - B., Divband (J Biomed Phys Eng, 2020)
BACKGROUND: Gadolinium oxide nanoparticles as positive contrast material of magnetic resonance imaging (MRI) have attracted a great attention due to the appropriate magnetic properties. One of the most desirable features of these nanoparticles is their ability of doping with other lanthanides which can change their properties. OBJECTIVE: This study aimed to investigate the effect of neodymium doping on MRI relaxivity of the gadolinium oxide nanoparticles. MATERIAL AND METHODS: In this experimental study, the oleic acid coated gadolinium oxide nanoparticles and the neodymium doped nanoparticles were prepared by polymer pyrolysis method. X-ray diffraction test and scanning electron microscopy were used for characterization of the particles. 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was performed to investigate the in vitro cell toxicity of the nanoparticles. The r1 and r2 relaxivities were extracted from the T1 and T2 weighted MR images, respectively. RESULTS: The average size of the cytocompatible spherical-like shape nanoparticles was 40 nm. The neodymium doped nanoparticles produced a significant decrease in the r1 relaxivity, and a 1.7 fold increase in the r2 relaxivity compared to the gadolinium oxide nanoparticles. CONCLUSION: Doping of neodymium into the gadolinium oxide nanoparticles suppresses the r1 relaxivity and enhances the r2 relaxivity of the nanoparticles.